SIMULASI SELF DEFENSE SEBAGAI SARANA PEMBELAJARAN MENGHADAPI PEMBAJAKAN PESAWAT KOMERSIAL MENGGUNAKAN METODE FRAME BY FRAME - Nurcahyani Dewi Retnowati; Zikri Mardhatillah (Compiler, 2015)
Self defenseis a system for defending selfwhich is used to defeat the opponent quickly and without spending a lot of energy. Self defense training is also very needed for pilots and flight attendants, for example to confront the hijacking of commercial flight.Self defense can be trained through the medium of interactive multimedia with 3D animation content. This interactive multimedia was built  by using adobe flash professional software, and 3D content using Lightwave 3D software. The result gets from trials to 30 respondents is this learning simulation is used because it is worth more than 50% of users give good response to simulation as a whole.